The Linguistics of Humour in Juyūt al-‘ankabūt and Sundūq al-dunyā of Ibrāhīm ‘Abd al-Qādir al-Māzinī - Mohamed Saad, Saad (Anaquel de Estudios Árabes, 2007)
Humorous statements can be analysed as a social reaction to violations of certain social rules. Hence our classification of humorous statements in two categories: those that violate a certain rule of language and those that contradict the receiver expectations by violating what we call “the logic of society”.
Keywords: Humour; Linguistics of humour; Al-Mā zin&#299